Financing needs to achieve Nationally Determined Contributions under the Paris Agreement in Caribbean Small Island Developing States - Mohan, Preeya S. (Mitigation and adaptation strategies for global change, 2023)
Caribbean Small Island Developing States (SIDS) are highly vulnerable to the impacts of climate change. Given high mitigation and adaptation costs and constrained domestic finances, they seek international funding to meet their climate objectives. This paper investigates Caribbean SIDS perspectives on the role of international climate finance in addressing climate change and its effectiveness in meeting climate goals. The paper first explored the climate financing needs of sixteen Caribbean SIDS through a content analysis of their Nationally Determined Contributions (NDCs). It then compares the climate finance needs of the region with international climate finance commitments received by examining climate finance trends using data from the Organization for Economic Cooperation and Development (OECD) Development Assistance Committee’s (DAC) Creditor Reporting System (CRS). The study revealed large gaps in estimating the climate finance needs of the region, as well as important patterns in the way climate finance is being distributed across mitigation, adaptation and overlap activity; principal versus significant climate objective; recipient country; sector; and source and type of funding. These findings are useful to help countries make decisions about how international climate finance should be used, and how its impacts should be evaluated and a basis for climate finance negotiations and dialogue with bilateral development partners and multilateral climate funds, and to assess whether available funds are being put to good use and identify problems that need to be addressed.